PENGARUH PROFITABILITAS, SOLVABILITAS DAN DIVIDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2022 - Saragih, Rudy Hedianton; Lumigar, Asrinita Hedianton; Saragih, Kuncu; Napitupulu, Bertha Elvy; Panjaitan, Yunia (Journal of Information System, Applied, Management, Accounting and Research, 2024)
Companies that have gone public will be listed on the Indonesia Stock Exchange, and offer their shares to the public. Most banking companies are listed on the Indonesia Stock Exchange. Banking sector stocks attract investors' attention. Investors consider stock prices before making an investment. The share price is a reflection of the company. If the company's financial performance is good, the shares will be in demand by investors. To anticipate mistakes in determining the company in investing, investors can check the company's performance by assessing financial ratios. Financial ratios can be obtained from the company's financial statements. Financial ratios such as profitability ratios and solvency ratios can affect the company's share price. Investors in investing want to get dividends from the shares purchased. By getting dividends, investors can decide to reinvest. The purpose of this study was to determine the effect of profitability, solvency, dividends on stock prices in banking companies listed on the Indonesia Stock Exchange in 2018-2022 either partially or simultaneously. The results showed that partially profitability as measured by ROA and dividends as measured by DPR had an effect on stock prices in banking companies listed on the Indonesia Stock Exchange in 2018-2022. Solvency as measured by DER has no effect on stock prices in banking companies listed on the Indonesia Stock Exchange in 2018-2022. Simultaneously profitability, solvency, dividends affect the share price of banking companies listed on the Indonesia Stock Exchange in 2018-2022.